Morbidly Adherent Placenta in Mid Trimester Abortion - A Case Report (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Morbidly adherent placenta (MAP) occurs when there is abnormally firm attachment of placental villi to the uterine wall with the absence of the normal intervening decidua basalis and nitabuchs layer. There are several risk factors of this condition including previous uterine surgery like myomectomy, dilatation and curettage operation, placenta praevia following previous caesarean section, advanced maternal age, multiparity and tobacco use. A diagnosis of MAP can be confirmed with tissue histology; however, medical imaging can be effective diagnostic tool. USG can detect the presence of accreta (80% sensitivity) and absence of accreta (95% specificity). This condition is presented here as a 20 weeks pregnancy with missed abortion with morbid adherent placenta (MAP).Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 50-53